Prurigo nodularis, prurigo chronica új terápiás lehetőségei - Csörgő Sándorné Bata Zsuzsanna (BŐRGYÓGYÁSZATI ÉS VENEROLÓGIAI SZEMLE, 2021)
Prurigo nodularis (PN) is a skin disease that develops on chronically itchy skin. There are various causes behind the chronic itch. Due to intensive research in recent years different mechanisms that can participate in the development of chronic pruritus have been discovered, opening up new therapeutic targets for treatment. Here we review the various mechanisms behind chronic pruritus and discuss the novel therapies for PN.